Encapsulation Strategy on All Inorganic Perovskites for Stable and Efficient Photoelectrocatalytic Water Splitting. Issue 13 (4th June 2021) - Li, Linjuan; Gan, Liyong; Zhang, Zhonghai
Abstract: All inorganic perovskite CsPbBr3 nanocrystals are a promising candidate as photocathode for efficient photoelectrocatalytic (PEC) water splitting. However, the poor chemical stability severely limits its practical applications. The exploration of perovskite‐based ideal photocathode materials with efficient and highly stable PEC performance is still an ambitious and meaningful challenge. Herein, under guidance of theoretical calculations, an encapsulation strategy is proposed to prepare the CsPbBr3 /Ni2 P core/shell nanostructures. Compared with the pristine CsPbBr3 nanocrystals, the CsPbBr3 /Ni2 P nanostructures show a significant improvement of photocurrent density up to 10 000 folds with long‐term stability in aqueous solution, and present superior PEC activity for hydrogen generation with nearly 100% faradic efficiency. The encapsulation strategy opens up an avenue for rational design of perovskite‐based photocathodes for efficient and stable PEC water reduction. Abstract : All inorganic perovskite CsPbBr3 nanocrystals are embedded in bulk Ni2 P phase to form CsPbBr3 /Ni2 P core/shell nanostructures, which significantly improve the photocurrent density up to 10 000 folds and implement highly stable photoelectrochemical water reduction due to the formation of charge channel of Br‐P bonds between CsPbBr3 and Ni2 P.